Дослідження на городищі скіфського часу біля с. Циркуни на Харківщині у 2008 р. - Пеляшенко, К.Ю.; Крютченко, О.О. (Археологічні дослідження в Україні, 2009)
The paper presents the results of 2008 excavations at the Scythican time hill-fort near Tsyrkuny village of Kharkiv Oblast. The works concentrated at two lots: at the Trench 6, in a cultural layer of a south-eastern part of the First yard, and at the Trench 8, in a line of a rampart and a ditch in the north-eastern area of the First yard. Obtained results allow the authors to propose a new date of the hill-fort foundation and to trace the dynamics of its development.